Pelaksanaan Pembelajaran Peserta Didik Berkebutuhan Khusus di Sekolah Inklusif Selama Pandemik Covid-19 - Prasetyo, Teguh; Supena, Asep (Musamus Journal of Primary Education, 2021)
Learning activities during the Covid-19 pandemic are a new challenge for teachers in schools. especially special companion teachers or GPK in inclusive primary schools. GPKs still have to provide maximum service related to the learning process carried out during the Covid-19 pandemic. The purpose of this study was to obtain information related to the implementation of learning for students with special needs (PDBK) in inclusive schools during the Covid-19 pandemic. The research was conducted using a qualitative approach to the type of case study. The subjects studied were three GPKs in the Kreativa Inclusive Elementary School, Bogor City. Data collection was obtained through questionnaires and semi-structured interviews conducted online. Data analysis was carried out in a descriptive qualitative manner with the help of nvivo 12 plus. The results showed that the PDBK learning during the Covid-19 pandemic was as follows; (1) the GPK has prepared learning tools, especially individual learning programs, (2) offline learning in classrooms and center rooms focus on developing PDBK life skills, (3) learn the content is the same as before the pandemic, (4) online learning is carried out through the zoom application and WhatsApp, and (5) the process of assessing learning outcomes using google forms and worksheets related to PDBK learning activities. The learning challenges during the Covid-19 pandemic faced by GPK, namely; decreased learning outcomes of PDBK, problems with GDPK tantrums during online learning, and communication problems to provide an understanding of learning.